Solvent effect on the nonlinear absorption of 5,10-A2B2 meso substituted porphyrins - SENGE, MATHIAS; BLAU, WERNER; WANG, JING (My University, 2013)
The effect of the solvent on the nonlinear absorptive properties of two series of 5,10-A 2 B 2 porphyrins was investigated with an open Z-scan technique in the ns time regime. The recorded responses, which varied between compounds and solvents, were fitted to a four-level model where the one-photon excited state absorption is followed by a two-photon process arising from the higher excited states. For most of the compounds the positive nonlinear absorption in toluene was stronger than that in DMF and chloroform. This was attributed to enhanced two-photon absorption in toluene. For DMF and chloroform the solvent effects were most likely to be compound specific. It was demonstrated that the high saturation intensity of two-photon absorption shifts the RSA/SA turnover into a higher fluence range, which is desirable for optical limiting applications. This saturation intensity of two-photon absorption varied between compounds and solvents. Additionally, nonlinear scattering contributed strongly to the open Z-scan responses for many compounds in chlorobenzene and chloroform ? chlorobenzene solutions. This was associated with the photodegradation of chlorobenzene.
PUBLISHED
Keywords: Chemistry; Nanoscience & Materials